2023
DOI: 10.1039/d2cp05600c
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and control of the exciton-recombination region of thermal-stressed blue organic light-emitting diodes

Abstract: Organic light-emitting diodes (OLEDs) suffer from carrier imbalance under high temperature. We improved their thermal stability by using the space interlayers adjacent to charge transport layers. The current efficiency of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Although the mobility at 80 °C is 0.47 × 10 −4 cm 2 V −1 s, which is decreased compared to those at other temperatures, it is still 6.7 times higher than that of our previously reported device using low T g material of 1,3,5‐tris(1‐phenyl‐1H‐benzo[d]imidazol‐2‐yl)benzene (TPBi, T g = 122 °C) as the functional material. [ 33 ] The results indicated that owing to the stable physical and chemical properties of the materials with better heat resistance, effective carrier transport was guaranteed and the thermal stability of the devices was enhanced. In addition, interfacial morphology was maintained under high temperatures, which further contributed to the enhanced thermal stability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the mobility at 80 °C is 0.47 × 10 −4 cm 2 V −1 s, which is decreased compared to those at other temperatures, it is still 6.7 times higher than that of our previously reported device using low T g material of 1,3,5‐tris(1‐phenyl‐1H‐benzo[d]imidazol‐2‐yl)benzene (TPBi, T g = 122 °C) as the functional material. [ 33 ] The results indicated that owing to the stable physical and chemical properties of the materials with better heat resistance, effective carrier transport was guaranteed and the thermal stability of the devices was enhanced. In addition, interfacial morphology was maintained under high temperatures, which further contributed to the enhanced thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…While in our previous study, the current densities at different temperatures were 1.06, 1.90, 2.26, and 1.85 mA cm −2 , and the luminous intensities at different temperatures were 99.88, 200.5, 273.3, and 248 cd m −2 , respectively. [ 33 ] This indicated that the thermal stability was significantly enhanced. In Figure 3b, the OLED annealed at 80 °C reaches exciton complex equilibrium faster compared to that annealed at 100 °C, which is reflected in the larger current efficiency (CE) obtained at the low brightness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, this indicates that the emissions of device A1-A4 both originate from the exciton recombination region between TAPC and LiF/Al, this is consistent with the above discussion. In other words, using DNA-CTMA as the EBL, the charge balance enables efficient confinement of the exciton within Alq 3 layer, and the region of exciton recombination is consistently confined to within the Alq 3 layer, although there is a certain displacement of the recombination region [24].…”
Section: Photoelectric Performance Of Green Alq 3 Bioledsmentioning
confidence: 99%